Mindful parenting and parental bonding as protective factors of parenting stress in mothers of children with cerebral palsy - Hidayah, Nurul; Putri, Sheila Zulfiani (Insight: Jurnal Ilmiah Psikologi, 2023)
This study examines the effect of mindful parenting and parenting bonding simultaneously or partially in decreasing parenting stress in mothers of children with cerebral palsy in Yogyakarta. This study used a quantitative survey method by utilizing three psychological scales: the Parenting Stress Scale, the Mindful Parenting Scale, and the Parenting Bonding Scale. The study population consisted of women who were members of the cerebral palsy community in Yogyakarta. A total of 38 samples were obtained using a simple random sampling technique. Multiple linear regression analysis was used to test the hypothesis. The findings revealed that (1) mindful parenting and parenting bonding significantly affected parenting stress (F = 9.890; R = 0.601; p < 0.01); (2) there was a significant negative effect of mindful parenting on parenting stress (t = -2.745; partial r = -0.115; p < 0.01); and (3) parental bonding did not significantly affect parenting stress (t = -0.684; r partial = -0.684; p > 0.05). Together, mindful parenting and parenting bonding can help decrease parenting stress by 36.1%, with mindful parenting contributing 30.15% to decreasing stress. These results suggest that mindful parenting and parenting bonding are highly protective factors against parenting stress for mothers raising children with cerebral palsy in Yogyakarta